Profiling the TPACK Mastery of English Pre-Service Teachers for 21st Century Learning - Precilia Rafra; Ince Rezky Naing; Michael Laurenz Christy Menanti (Universitas Islam Negeri Palopo, 2025)
The present research seeks to examine the extent of Technological Pedagogical Content Knowledge (TPACK) competence demonstrated by English pre-service teachers enrolled in the Faculty of Teacher Training and Education at Cenderawasih University, as well as to identify the most dominant and the weakest aspects of their TPACK competence. The background of this study is grounded in the demands of 21st-century learning, which underscores the holistic incorporation of content, pedagogy, and technology within the instructional process. A quantitative survey method was employed, using a purposive sampling technique involving final-semester students of the English Education Study Program. The data were gained through a TPACK questionnaire encompassing seven key dimensions: Technological Knowledge (TK), Content Knowledge (CK), Pedagogical Knowledge (PK), Pedagogical Content Knowledge (PCK), Technological Content Knowledge (TCK), Technological Pedagogical Knowledge (TPK), and TPACK. The data in this study were subjected to descriptive analysis using SPSS version 29 software. The findings reveal that the overall level of TPACK mastery among the students falls into the “moderate” category. The most dominant aspect is Content Knowledge (CK), which achieved a high average score, indicating strong mastery of English content, particularly in speaking and listening skills. Conversely, the weakest aspect is Technological Knowledge (TK), which obtained a low average score, consequently affecting the integrative dimensions such as TPK, TCK, and TPACK, which remain at a moderate level. In conclusion, the study affirms that English pre-service teachers possess a strong grasp in content and pedagogical knowledge but still face limitations in technological competence. Therefore, it is recommended that technological proficiency be strengthened through intensive training, the incorporation of technology-oriented practices within the curriculum, ongoing mentorship programs, and extended research efforts to yield a more holistic understanding of TPACK mastery profiles among pre-service teachers.